Respons Pertumbuhan Awal Tebu (Saccharum officinarum L.) pada Berbagai Posisi Bagal Batang dalam Perbanyakan Vegetatif - Refki Sanjaya; Retno Wulan Sari; Muamar Kadafi (Universitas Muhammadiyah Kotabumi, 2026)
Sugarcane (Saccharum officinarum L.) is a strategic plantation crop contributing significantly to global sugar production. Early growth performance is a critical phase determining stand establishment and subsequent productivity, particularly in vegetative propagation systems using stem cuttings (setts). This study aimed to evaluate the early growth performance of the RGM 1010 Cultivar of sugarcane based on different stem sett positions (top, middle, and bottom) using a Randomized Complete Block Design with four replications. The experiment was conducted from July 2025 to January 2026 at the Experimental Farm of Politeknik Negeri Lampung, Indonesia. Observed parameters up to 10 weeks after planting (WAP) included survival percentage, plant height, number of leaves, leaf length, and number of internodes. Analysis of variance at the 5% significance level showed that sett position significantly affected survival percentage and plant height. The top setts produced the highest survival rate (92.5%) and plant height (153.5 cm), followed by middle and bottom setts. In contrast, number of leaves, leaf length, and number of internodes were not significantly influenced by sett position. Pearson correlation analysis revealed a weak and non-significant negative relationship (r = –0.324) between plant height and leaf number, indicating that stem elongation and leaf formation were relatively independent during early growth. The superior performance of top setts is attributed to higher meristematic activity and hormonal balance, promoting faster shoot and root initiation. Overall, while all sett positions were viable for vegetative propagation, top setts demonstrated better early vigor, providing practical implications for improving seedling establishment efficiency in sugarcane cultivation.